2021
DOI: 10.1038/s12276-021-00564-4
|View full text |Cite
|
Sign up to set email alerts
|

SRF is a nonhistone methylation target of KDM2B and SET7 in the regulation of skeletal muscle differentiation

Abstract: The demethylation of histone lysine residues, one of the most important modifications in transcriptional regulation, is associated with various physiological states. KDM2B is a demethylase of histones H3K4, H3K36, and H3K79 and is associated with the repression of transcription. Here, we present a novel mechanism by which KDM2B demethylates serum response factor (SRF) K165 to negatively regulate muscle differentiation, which is counteracted by the histone methyltransferase SET7. We show that KDM2B inhibited sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For example, increased muscle glycogen and muscle fiber hypertrophy are two important phenomena of muscular adaptations to training that can affect strength and stamina of endurance horses respectively (Rivero, 2007). Interestingly, our results highlighted eight genes—ATPase sarcoplasmic/endoplasmic reticulum Ca 2+ transporting 2 ( ATP2A2 ), mitogen‐activated protein kinase 10 ( MAPK10 ), protein kinase AMP‐activated non‐catalytic subunit gamma 2 ( PRKAG2 ), myoferlin ( MYOF ), glutamate decarboxylase like 1 ( GADL1 ), lysine demethylase 2B ( KDM2B ), growth arrest specific 2 ( GAS2 ), and calcium voltage‐gated channel subunit α1 A ( CACNA1A )—as genes participating in muscle contraction (Ropka‐Molik et al, 2017), equine skeletal muscle adaptations to exercise (Bryan et al, 2017), muscular glycogenosis (Laforêt et al, 2006), muscle dystrophy regulation (Davis et al, 2000), regulation of muscle strength (Mahootchi et al, 2020), skeletal muscle differentiation (Kwon et al, 2021), muscle synthesis (Hu et al, 2021), and regulation of muscular hypotonia (Reinson et al, 2016) respectively. However, McQueen et al (2014) also revealed the contribution of an SNP (rs68536711) located in the equine MYOF gene in foals Rhodococcus equi infection susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased muscle glycogen and muscle fiber hypertrophy are two important phenomena of muscular adaptations to training that can affect strength and stamina of endurance horses respectively (Rivero, 2007). Interestingly, our results highlighted eight genes—ATPase sarcoplasmic/endoplasmic reticulum Ca 2+ transporting 2 ( ATP2A2 ), mitogen‐activated protein kinase 10 ( MAPK10 ), protein kinase AMP‐activated non‐catalytic subunit gamma 2 ( PRKAG2 ), myoferlin ( MYOF ), glutamate decarboxylase like 1 ( GADL1 ), lysine demethylase 2B ( KDM2B ), growth arrest specific 2 ( GAS2 ), and calcium voltage‐gated channel subunit α1 A ( CACNA1A )—as genes participating in muscle contraction (Ropka‐Molik et al, 2017), equine skeletal muscle adaptations to exercise (Bryan et al, 2017), muscular glycogenosis (Laforêt et al, 2006), muscle dystrophy regulation (Davis et al, 2000), regulation of muscle strength (Mahootchi et al, 2020), skeletal muscle differentiation (Kwon et al, 2021), muscle synthesis (Hu et al, 2021), and regulation of muscular hypotonia (Reinson et al, 2016) respectively. However, McQueen et al (2014) also revealed the contribution of an SNP (rs68536711) located in the equine MYOF gene in foals Rhodococcus equi infection susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, their physiological role in normal condition is still poorly understood. So far, only the role of KDM2B have been studied in skeletal muscle, although KDM2B its absent in adult skeletal muscle ( Kwon et al, 2021 ). KDM2B is highly expressed in muscle during late embryonic development and constantly decreases in skeletal muscle tissue with the age, supporting the idea that KDM2B needs to be silenced to achieve muscle differentiation.…”
Section: Jmjd: Jumonji C—domain Demethylases and Skeletal Muscle Rege...mentioning
confidence: 99%
“…Interestingly, ChIP experiments performed in myoblasts overexpressing KDM2B, revealed that H3K4me3 levels were not altered on muscle specific promoters. Mechanistically, KDM2B seems to act through the serum response factor (SRF) since it was shown to demethylate SRF, thus preventing its binding to the serum response elements (SRE) present in the promoters of muscle specific genes ( Kwon et al, 2021 ) ( Table 1 , Figure 2C ).…”
Section: Jmjd: Jumonji C—domain Demethylases and Skeletal Muscle Rege...mentioning
confidence: 99%
See 1 more Smart Citation
“… Matsuzaki et al (2003) , for instance, have discovered that lysine residue 147 of SRF can be SUMOylated, which suppresses its transcriptional activity likely by interfering with its DNA binding potential. More recently, Kwon et al (2021) have reported that lysine residue 165 of SRF can be methylated by SET7 and de-methylated by KDM2B; dynamic SRF methylation is proposed to regulate its affinity for target promotes and contribute to muscle differentiation. By far, phosphorylation represents the most extensively characterized PTM for SRF.…”
Section: Introductionmentioning
confidence: 99%